Modified Composite Thermal Control Coatings Irradiated with High−Energy Particles - Harutyunyan, V. V.; Badalyan, A. O.
The main trends in modern space instrumentation are an increase in the active life of spacecraft, the tightness of their structure, and the widespread use of new polymer composite materials. Composite thermoregulatory coatings are designed to maintain the required thermal regime of objects by establishing a balance between the energy absorbed from the outside and the energy emitted into the environment. The aim of this work is to study the structure of new composite thermoregulatory materials (coatings) irradiated with high−energy particles − an electron with an energy of 3.5 MeV and a proton with an energy of 18 MeV, using X−ray diffraction analysis, optical photoluminescence doped with cerium, as well as other coatings, a new composition of thermoregulatory coatings (TRC) was developed by the method of hydrothermal microwave synthesis. According to the results of studies of modified TRCs, it was found that the samples synthesized by the microwave method have a crystalline structure after heat treatment. It is shown that the mechanisms of the effect of radiation spectra on the material medium are completely different and are determined by the atomic−molecular structure of matter. Irradiation with highly energetic particles gives rise to color defect centers of two types.
Keywords: Physics